Transgenic Mouse Expressing Optical MicroRNA Reporter for Monitoring MicroRNA-124 Action during Development - Choi, Yoori; Hwang, Do won; Kim, Mee Young; Kim, Joo Yeon; Sun, Woong; Lee, Dong Soo (Frontiers in Molecular Neuroscience, 2016)
MicroRNAs (miRNAs) fine-tune target protein synthesis by suppressing gene expression, temporally changing along development and possibly in pathological conditions. A method to monitor the action of miRNAs in vivo shall help understand their dynamic behavior during development. In this study, we established a transgenic mouse harboring miR-124 responsive element in their luciferase-eGFP reporter transgenes which enabled monitoring the action of miR-124 in the brain and other organs in vivo by the bioluminescence imaging. The mouse model was produced and verified by imaging ex vivo so that luminescence by luciferase shone and then reduced during development with miR-124 expression. Bioluminescence dramatically decreased in the brain between embryonic day 13 and 16 as endogenous miR-124 expression increased, which sustained into adulthood. The inverse relationship of miR-124 expression was observed with luciferase bioluminescence and activity ex vivo as well as in vivo. Taken together, one can use this microRNA-transgenic mouse to investigate the temporal changes of microRNA action in vivo in the brain as well as in other organs.